Spectral Analysis of Individual Terrestrial Gamma‐Ray Flashes Detected by ASIM. Issue 23 (6th December 2021) - Lindanger, A.; Marisaldi, M.; Sarria, D.; Østgaard, N.; Lehtinen, N.; Skeie, C. A.; Mezentzev, A.; Kochkin, P.; Ullaland, K.; Yang, S.; Genov, G.; Carlson, B. E.; et al.
Abstract: The Atmosphere‐Space Interactions Monitor (ASIM) is the first instrument in space specifically designed to observe terrestrial gamma‐ray flashes (TGFs). TGFs are high energy photons associated with lightning flashes and we perform the spectral analysis of 17 TGFs detected by ASIM. The TGF sample is carefully selected by rigorous selection criteria to keep a clean sample suitable for spectral analysis, that is, suitable count statistics, low instrumental effects, and reliable source location. Monte Carlo modeling of individual TGFs has been compared to the observed energy spectra to study the possible source altitudes and beaming geometries. A careful model of the instrumental effects has been developed and validated. Several combinations of source altitudes and beaming geometries are accepted by the statistical tests for all the TGFs in the sample resulting in a large uncertainty in the estimate of the intrinsic source luminosity. The analyzed TGFs show significant variations in observed fluence independent of the distance between source and ASIM. A lower limit on the maximum photon energy produced by TGFs is estimated to be 24 MeV for the analyzed TGFs. The intrinsic limitations of TGF spectral analysis from space are also investigated and it is found that the ability to constrain the source altitude and beaming geometries of TGFs strongly depends on the distance between source and satellite. With the current generation of instruments with effective areas in the range of few hundreds cm 2, it is very difficult to constrain reliably the source properties without the help of simultaneous measurements in the radio band. Key Points: Spectral analysis of individual terrestrial gamma‐ray flashes (TGFs) detected by the Atmosphere‐Space Interactions Monitor is performed Source properties such as altitude, beam size and intensity are explored, showing it is difficult to constrain the source parameter space Limitations on TGF spectral analysis due to count statistics are investigated